2019
DOI: 10.1016/j.istruc.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to local imperfections in inelastic thin-walled rectangular hollow section struts

Abstract: Mass efficient inelastic thin-walled rectangular hollow section (RHS) struts practically always fail in a combination of local-global interactive buckling and material nonlinearity while also exhibiting high sensitivity to initial imperfections. Nonlinear finite element (FE) models for inelastic thin-walled RHS struts with pre-defined local and global geometric imperfections are developed within the commercial package Abaqus. Using a unified local imperfection measurement based on equal local bending energy, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Because of the complicated profile shape (deep corrugations on the surface), an indirect method for detection of buckling and local instabilities formation was employed. The method is based on the observation of equilibrium path nonlinearities in the phase II pre-buckling elastic range instead of the classic approach [22][23][24][26][27][28][29][30] that relies on the determination of the plastic hinges' geometry. Phase I is a pre-buckling elastic range and ends when the yield strength f y = 337 MPa is achieved, transiting to the phase II pre-buckling elastoplastic range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the complicated profile shape (deep corrugations on the surface), an indirect method for detection of buckling and local instabilities formation was employed. The method is based on the observation of equilibrium path nonlinearities in the phase II pre-buckling elastic range instead of the classic approach [22][23][24][26][27][28][29][30] that relies on the determination of the plastic hinges' geometry. Phase I is a pre-buckling elastic range and ends when the yield strength f y = 337 MPa is achieved, transiting to the phase II pre-buckling elastoplastic range.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge about the local instability formation mechanism is useful for predicting the entire structure's stability and load-carrying capacity and particularly useful for spotting the nature and place of damage. Scientific studies on the subject [26][27][28][29] have made a significant contribution to the development of science and technology, but they are usually related to flat-walled profiles of regular geometry. Determination of the failure mechanism becomes more complicated with irregular geometry such as the double-corrugated one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of deformations of box complexes with the graph theory showed satisfactory agreement between the experimental results and numerical calculations for the values of the horizontal and vertical deflection of the wall, as well as for the experimental, calculated and numerical characteristics of the bending moment, and not only for closed but also unclosed box profiles [7]. Local defects additionally increase the sensitivity of profiles of a rectangular hollow section to the creation of a shape error [8].…”
Section: Introductionmentioning
confidence: 86%
“…and Farsi, M [25]. Shen, J. and Wadee, M.A [26] probed the local and global geometric imperfections effect on mechanical behaviour of inelastic thin-walled rectangular hollow struts by nonlinear finite element (FE) models.…”
Section: Literature Review On Geometrical Imperfection Analysismentioning
confidence: 99%